Shell morphology of the unionid mussels (Anodonta anatina, Unio pictorum and U. tumidus) in relation to gender and trematode parasitism - Moteka, Ebenezar Njimerie (2015)
Freshwater mussels (Unionoida) show great variability in shell morphology which can be associated with differences in habitat, sex and/or parasite infection. Three unionid mussel species, (Anodonta anatina, Unio pictorum and Unio tumidus) were collected from two sites Lake Saravesi, (Laukaa) and Lake Kuivasjarvi, (Oulu), between May - October 2012. Intraspecific trends that were associated with the mussels’ sex and/or parasites infection were studied and observations were made on how sex and parasite infection could have a role in shells morphological characters/patterns. The study revealed a range of morphometric differences among and across populations, as well as, within and between species. The hypothesis that female growth would decrease relative to males at adult ages due to energetic cost of glochidium larvae production did not receive unequivocal support. In addition, the hypothesis of adult female shells being wider (more inflated) than that of males due to space requirements by carried glochidia was also supported only in A. anatina of Lake Kuivasjärvi but not in Lake Saravesi, or in other mussel species. Male A. anatina were higher than females in Lake Saravesi, but not in Lake Kuivasjärvi, or in other mussel species, except for U. pictorum, in which females were higher than males among the large individuals. Between species, A. anatina had the highest shell, followed by U. tumidus and U. pictorum, while U. tumidus had the widest shell, followed by U. pictorum and A. anatina. The hypothesis of trematode infected mussels being wider due to space requirements by growing parasites was supported partly: mussels infected by R. fennica were, indeed, wider than the uninfected individuals, but for mussels infected with R. campanula this pattern was not found. On the other hand, R. campanula–infected individuals were relatively longer (more elongated) than the uninfected mussels. This may indicate a parasite species specific interaction between parasitism and host mussel shell morphology.